PERBANDINGAN HASIL BELAJAR DAN PENGUASAAN KONSEP FISIKA SISWA ANTARA PENGGUNAAN SIMULASI DAN EKSPERIMEN - Linda Retnowati; I Dewa Putu Nyeneng; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
Based on the research conducted there are many teachers who use conventional learning so that students are difficult to accept, respond, and develop materials provided by the teacher. The purpose of this study to determine: 1) The average difference the students 'physics learning outcomes between using simulation and experimental (2) The average difference the students 'physics learning outcomes between using simulation and experimental. This research has been carried out in the school year 2012/2013 in SMPN 1 Kotagajah. The study population was all students in class IX during the second semester.The samples taken while the IXB class as a class that uses experimental methods and IXF class as a class that uses simulation methods. Sampling technique in this study using cluster random sampling technique. Design of Experiments in this study using the form One-Shot Case Study. The results of the research conducted is: (1) There is a difference average physics student learning outcomes between using simulations and experiments that are 80.5 in the experimental class dan 70 in the simulation class (2 ) There is a difference average the students' mastery of physics concepts between using simulations and experiments that are 72.38 in the experimental class and 68.10 in the simulation class. So we can conclude the results of study and mastery of the concepts of physics experiments grade higher than the simulation.Kata kunci: eksperimen, hasil belajar, penguasaan konsep, simulasi